The fabrication of monodisperse polypyrrole/SBA-15 composite for the selective removal of Cr(vi) from aqueous solutions. (21st April 2021) - Wang, Liang; Gao, Peng; Liu, Mengxin; Huang, Ziqing; Lan, Shixia; Li, Yue; Rao, Wenhui; Liu, Yuanli; Du, Rui; Yu, Chuanbai
Abstract : Monodisperse polypyrrole/SBA-15 composite (PPy/SBA-15) was fabricated by in situ polymerization and used for Cr(vi ) adsorption from aqueous solution. Abstract : Monodisperse polypyrrole/SBA-15 composite (PPy/SBA-15) was fabricated by in situ polymerization and used for Cr(vi ) adsorption from aqueous solution. PPy/SBA-15 was characterized by numerous approaches. Factors affecting the Cr(vi ) adsorption process, including the pH, the dose of adsorbent and contact time, were analyzed through batch experiments. The optimum experimental conditions were pH 2, dose of 4 g L −1 and contact time of 300 min. Meanwhile, PPy/SBA-15 had strong selective adsorption of Cr(vi ) in co-existing ionic solution, the adsorption kinetics matched a pseudo-second-order kinetic model, and the adsorption isotherm data followed Langmuir adsorption isotherm models with a maximum adsorption capacity of 194.17 mg g −1 at 298 K, which is higher than that found in other reports of the same type of adsorbent. Regeneration evaluation demonstrated that the adsorbent can be recycled four times, retaining 92.58% of its removal rate. Moreover, EDX indicated that PPy/SBA-15 adsorbed Cr(vi ) on its surface owing to ion exchange of chloride ions with either HCrO4 − or Cr2 O7 2− . XPS further certified that part of Cr(vi ) was reduced to Cr(iii ). Overall, PPy/SBA-15 possesses capability as an alternative adsorbent to remove Cr(vi ) from aqueous solution.